(untitled) (Analele Universităţii Bucureşti. Limbi şi Literaturi Străine, 2024)
The language of German newspapers in Romania exhibits properties which reflect the synergy that led to the genesis of the present form of this variety of the German language. One main trait consists of preserving the stilistic neutrality of words that are now obsolete in Germany or Austria, hence the effortless play of synonyms that belong to different registers throughout the other German-speaking countries. However, the language contact with Romanian may never be underestimated, and is also observable in respect to the norms that shape the way articles are written. Articles about King Michael I of Romania seem to highlight the fact that the culturally-influenced language norms are known and employed deliberately, of which some actually contrast to Romanian language-culture.